MENGGAGAS IDEOLOGI PERADABAN MODERN MELALUI PENGEMBANGAN TRADISI DAN NILAI-NILAI KEADABAN PESANTREN - Fathor Rachman (TADRIS: Jurnal Pendidikan Islam, 2015)
Abstract: Pesantren plays its roles by empowering the community and educating the nation through its education and socio-cultural tradition while maintaining its independence and consistency .The community acknowledges pesantren through its education uniqueness  has encouraged pesantren to continue as a catalyst and initiative of development in all aspects, especially in responding global developments. The existence of pesantren is established by  internalization of "panca-jiwa (five principles)" of pesantren, that are: simplicity, sincerity, independence, freedom and Islamic brotherhood. The traditions and values have formed the  existence of pesantren in the changes and dynamic inductrial and technological glabalization.  Keywords: ideology, modern civilization, traditions, moral values